2020
DOI: 10.1093/cid/ciaa1613
|View full text |Cite|
|
Sign up to set email alerts
|

A New Specimen for Syphilis Diagnosis: Evidence by High Loads ofTreponema pallidumDNA in Saliva

Abstract: Background DNA from many pathogens can be detected in saliva. However, the presence and quantity of Treponema pallidum DNA in syphilis patients in saliva is unknown. Methods A total of 234 syphilis patients with different stages and 30 volunteers were enrolled. Paired saliva and plasma samples were collected from all the participants. Consecutive saliva samples from 9 patients were collected every 4 hours following treatment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 24 publications
0
33
0
1
Order By: Relevance
“…Though the diagnosis of syphilis is mainly based on clinical manifestations combined with non- treponema and treponema serological tests, the detection of the nucleic acid of the pathogen from certain specimens is a direct method for the definite diagnosis of infectious diseases. According to previous studies, the detection rates of T. pallidum DNA in secondary syphilis patients reached 87.5 and 64.5% in saliva and oral swabs, respectively ( 4 , 7 ). Blood T. pallidum DNA was positive in suspected primary syphilis patients whose blood rapid plasma regain (RPR) and T. pallidum particle agglutination (TPPA) were nonreactive ( 3 ).…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Though the diagnosis of syphilis is mainly based on clinical manifestations combined with non- treponema and treponema serological tests, the detection of the nucleic acid of the pathogen from certain specimens is a direct method for the definite diagnosis of infectious diseases. According to previous studies, the detection rates of T. pallidum DNA in secondary syphilis patients reached 87.5 and 64.5% in saliva and oral swabs, respectively ( 4 , 7 ). Blood T. pallidum DNA was positive in suspected primary syphilis patients whose blood rapid plasma regain (RPR) and T. pallidum particle agglutination (TPPA) were nonreactive ( 3 ).…”
Section: Introductionmentioning
confidence: 81%
“…DNA was dissolved with 100 μL Tris-EDTA (TE) buffer. The presence and loads of polA and Tpp47 genes were measured by nPCR and ddPCR assays, which were performed as described in previous studies ( 3 , 4 ). For nPCR assay, there were 25 and 30 cycles in the first and second rounds of PCR, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this analysis we excluded men with local primary anal lesions and local primary oral lesions with the aim of capturing the pattern of T. pallidum shedding from these sites following systemic dissemination from a remote site of infection. In a recent study of individuals with syphilis by Wang et al , detection of T. pallidum from saliva and blood using droplet digital PCR both peaked during secondary syphilis, providing evidence that T. pallidum is shed from the oral mucosa following systemic dissemination 4. We postulate that T. pallidum may also be shed from the anal region following systemic dissemination; however, this needs to be verified in studies using assays that can detect blood and anal T. pallidum with high sensitivity.…”
Section: Discussionmentioning
confidence: 97%
“…These findings suggest the secondary stage of syphilis may be the most infectious. Several other recent studies have also found oral detection of T. pallidum to be common during the secondary stage of syphilis; however, none of these studies has also tested all men for concurrent anal T. pallidum 4–6…”
Section: Introductionmentioning
confidence: 99%